Instincts as Sedimentation in E. Husserl’s Phenomenology - Jonkus, Dalius (Problemos, 2024)
Husserl’s concept of instincts transformed the concept of intentionality, supplemented the concept of teleology of consciousness, and shed new light on the problem of the relationship between irrationality and rationality. This article analyses Husserl’s phenomenology of instincts through the prism of the concept of sedimentation. I argue that instincts can be understood as sedimentation, as a pattern of the transformation of consciousness into unconsciousness, and the transformation of unconsciousness into consciousness. The concept of instincts as sedimentation helps to understand how skills are preserved and transmitted from generation to generation, and how unconscious instincts work in our conscious experience.